The Influence of Volley Training Method and Agility on Tennis Players’ Backhand Volley Accuracy - Utomo, Noor Setya; Sulaiman, Sulaiman; Nasuka, Nasuka (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The result of observation in UNWAHAS College Tennis Club, backhand volley placement skill has not been optimal yet. The objective of this research are to find out the influence of training method on backhand volley’s accuracy; the influence of agility on students’ agility; interaction between training method and agility on backhand volley’s accuracy. The method used in this research is experimental method with 2x2 factorial experiment design. Sample collection method used is purposive sampling, thus obtained 20 people as sample. The Independent variables of this research are training method and accuracy while the dependent variable is shot accuracy. The result of the research indicated that there is difference in the influence of Volley training method in backhand volley accuracy with the average of Volleys Against the Fence method is 20.8 and the average of Down The Line Volley is 15.5. Further test to find out the difference between cells conducted through Tukey test can be concluded that volleys against the fence training method would be better given to the tennis players with high agility, rather than layers with low agility. Conclusion: there is difference of training method and agility on backhand volley accuracy.